Oxidative Stress Promotes Eating Behavior and Obesity in C. elegans via EGL-4 / DAF-16 Signaling - Wensheng Li; Eric Blough; Cuifen Wang; Larry Dial; Omolola Olajide; Randa Al-Jayoussi; Nesreen BenHamed; Miaozong Wu (Journal of Pharmacy and Nutrition Sciences, 2015)
Oxidative stress is associated with pathophysiological progress of many diseases. The objective of study was to investigate whether increased environmental oxidative stress stimulation can promote excessive eating behavior, a common cause of obesity, and to identify the molecular mechanism.The cGMP-dependent kinase (PKG) activator 8-pCPT-cGMP was applied in worm swimming assay to study behavior shifting between quiescence and foraging in C. elegans. Genetically modified C. elegans (egl-4 loss or gain of function, and daf-16 mutant) were treated with paraquat, an oxidative stress inducer. Worm’s foraging behavior, body fat accumulation and body length were determined. The foxo1::gfp-transfectedHEK293 cells and C. elegans (daf-16::gfpTJ356) were further used to examine the effect of paraquat on PKG expression and FOXO nuclear translocation.A novel swimming assay using PKGactivator stimulation was developed, which allows the rapid and effective study of foraging behavior in C. elegans. Paraquat treatment significantly inhibited quiescence, promoted foraging behavior, increased body fat accumulation and body growth. These responses were associated with diminished PKG expression/activation and increased FOXO (DAF-16) nuclear translocation in both transfected C. elegans and HEK293 cells.Our data suggest that PKG/FOXO signaling may plays an important role in mediating oxidative stress-induced excessive eating behavior and obesity development.